Patterns of emergency shelters in coastal plains a case study after the great east Japan Earthquake and Tsunami in Higashi‐Matsushima City - Yuko Araki; Sotaro Tsuboi; Akihiko Hokugo (Japan Architectural Review, 2020)
Abstract It has been pointed out that during large‐scale disasters, some evacuees cannot receive necessary support since they evacuate to places other than the shelters pre‐designated by the government. This is due to the fact that prior evacuation plans do not match the actual evacuation situation, and that the information collection and support system are not examined thoroughly beforehand. This research aims to contribute to the provision of measures on how to prepare for the occurrence of non‐designated shelters and evacuees and provide immediate support activities for evacuees after a disaster. From a case study of events in Higashi‐Matsushima during the Great East Japan Earthquake, we examined the occurrence and causes of evacuation within the coastal plains and showed that non‐designated shelters were also found in flooded areas of coastal plains.